Pengaruh Model Problem Based Learning (PBL) Terhadap Hasil Belajar IPAS Siswa di Kelas V SD Inpres Bontoloe, Kec. Bontolempangan Kab. GOWA: Penelitian - Nurhidayana Jamil; Kaharuddin; Syarifah Aeni Rahman (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model on the learning outcomes of students in grade V of SD Inpres Bontoloe, Bontolempangan District, Gowa Regency. This study is an experimental study. It was conducted at SD Inpres Bontoloe, Bontolempangan District, Gowa Regency, with the research subjects being grade V students. This study was conducted for approximately 2 months. The data collection techniques used in this study were tests and documentation. However, before the data was analyzed, a prerequisite analysis test was first carried out, namely the normality test and the homogeneity test. The results of the study concluded that there was an effect of the use of the problem based learning model on students' learning outcomes in science. Based on the results of the average value (mean) shows that students' learning outcomes before being given treatment were 76 while the average value of students' learning outcomes after being given treatment was 97.5. In addition, from the results of the t-test, it was known that the calculated t value obtained was 34.013, which was smaller than the t-table value of 1.724. Because t count > t table, H0 is rejected and Ha is accepted, which means that the use of the Problem Based Learning (PBL) model can influence and improve student learning outcomes.